SEIMBANG DAN SYARAT-SYARAT PEMINANGAN PERSPEKTIF FUQOHA’ - Misbachul Fitri, Abdul Basit (USRATUNA: Jurnal Hukum Keluarga Islam, 2022)
Before carrying out an arranged marriage, it is continued according to syar'i, so as parents and interested parties it is highly recommended to find a balanced/equivalent family mate, in Islam it is called Kafa'ah or kufu'. The Ulama' agree that, kafa'ah in religious matters is a must to implement. However, kafa'ah from non-religious aspects such as heredity, wealth, occupation and others, is only a material consideration which does not result in a marriage having to be terminated. Research uses library research as a method in extracting data. namely a research by focusing on the source of the data obtained from the literature. Books and writings that are in accordance with the subject matter being researched, regarding the balance and requirements for proposing a Fuqoha' perspective. Proposals in the science of fiqh are called khitbah, meaning requests. Meanwhile, according to the term, it means a statement or request from a man to a woman to become his wife in the ways that apply in society. In proposing there are two conditions, there are mustahsinah conditions and customary conditions according to Fuqoha' which must be known and complied with by the groom and his family so that the proposal is perfect and does not experience legal defects.